Intrinsic kinetic parameters of Thermococcus onnurineus NA1 strains and prediction of optimum carbon monoxide level for ideal bioreactor operation. (February 2016) - Jeong, Yeseul; Jang, Nulee; Yasin, Muhammad; Park, Shinyoung; Chang, In Seop
Highlights: First report on intrinsic kinetic parameters of archaea. Optimum C L values for bioprocess development using NA1 strains are presented. Conditions required to maintain ideal bioreactor operation are predicted. General guidelines for designing large-scale bioreactors are provided. Abstract: This study determines and compares the intrinsic kinetic parameters ( K s and K i ) of selected Thermococcus onnurineus NA1 strains (wild-type (WT), and mutants MC01, MC02, and WTC156T) using the substrate inhibition model. K s and K i values were used to find the optimum dissolved CO ( C L ) conditions inside the reactor. The results showed that in terms of the maximum specific CO consumption rates ( q CO max ) of WT, MC01, MC02, and WTC156T the optimum activities can be achieved by maintaining the C L levels at 0.56 mM, 0.52 mM, 0.58 mM, and 0.75 mM, respectively. The q CO max value of WTC156T at 0.75 mM was found to be 1.5-fold higher than for the WT strain, confirming its superiority. Kinetic modeling was then used to predict the conditions required to maintain the optimum C L levels and high cell concentrations in the reactor, based on the kinetic parameters of the WTC156T strain.